Inovasi pembuatan panel dan batako berbahan serbuk kayu sebagai dinding rumah sederhana tahan gempa - I Nyoman Sutarja; I Made Dodiek Wirya Ardana; AAG Agung Yana; I Nyoman Susanta; IDGA Diasana (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2023)
The number of poor people in Indonesia in March 2021 was 27.54 million people. One indicator is that people do not yet have decent homes. The income of the poor is generally below average, resulting in difficulties in accessing housing loans from banks. All parties must contribute in helping the poor to have livable houses. Researchers innovate to make simple houses livable based on Appropriate Technology, namely technically meeting safety, economical and affordable, ergonomic according to occupant anthropometry, fulfilling socio-cultural standards so that they can be accepted by the community and are energy efficient and sustainable. The innovation of using panels or bricks from sawdust for the walls of a simple house with a size of 3 m x 6 m that was built according to Appropriate Technology methods meets feasibility. The maximum stress ratio of 0.534 occurs in the column and is smaller than the required 1.0. The maximum deviation that occurs at the top of the building is 5.91 mm and is smaller than 0.02 times the total height of the building, namely 0.02 times 4000 is 80 mm. Measurement of the intensity of natural lighting during the day obtained 338 Lux, room temperature obtained 25.56Â°C, air humidity (RH) 71.62%, and air movement 0.15 m/sec and noise 36.82 dB. The contribution of this research is to provide a new wall material solution for simple houses, namely walls made from panels and bricks made from wood powder.